Cross-Linguistic Influence on L2 Before and After Extreme Reduction in Input: The Case of Japanese Returnee Children - Kubota, Maki; Heycock, Caroline; Sorace, Antonella; Rothman, Jason (Frontiers in Psychology, 2020)
This study investigates the choice of genitive forms (the woman’s book vs. the book of the woman) in the English of Japanese-English bilingual returnees (i.e. children who returned from a second language dominant environment to their first language environment). The specific aim was to examine whether change in language dominance/exposure influences choice of genitive form in the bilingual children; the more general question was the extent to which observed behaviour can be explained by cross linguistic influence (CLI). First, we compared the choice of genitive form between monolingual Japanese speakers and bilinguals who had recently returned to Japan from an English monolingual environment. Second, we tracked changes in genitive preference within bilingual children, comparing their performances upon return to Japan to those of one year later. Results show that CLI alone is insufficient to explain the difference in genitive evaluation between bilinguals and monolinguals, as well as the intra-group bilingual variation over time. We suggest that both CLI and general processing considerations couple together to influence the changes in genitive preference.